(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2024)
The triumph of Western civilization which marked by significant industrial revolution through scientific breakthroughs and technological advancements still not necessarily make this civilization better as expected. With strongly emphasis on its pursuit of rationality, this civilization has faced criticism from numerous experts due to its various deficiencies and subsequent detrimental consequences. This article will investigate on how the notion of "envisioned civilization" can be realized by starting the process of its formation on the principle of moderation. The existence of moderation in the context of envisioning a civilization lies when civilization is driven by synthesizing Rationality, Morality and Spirituality in a balanced manner and taking roles for each other. Based on interdisciplinary approach, the study examines how the seamless incorporation of logical reasoning, ethical standards, and spiritual beliefs might enhance the development of a well-rounded and enlightened social structure. The findings demonstrate that by integrating these three dimensions harmoniously can support the limitation of rationality aspect, establishing a more comprehensive civilization